STUDY OF THE SOCIAL AND PHILOSOPHICAL VIEWS OF THE JADIDS OF TURKESTAN BY TURKISH SCIENTISTS (British Journal of Global Ecology and Sustainable Development, 2022)
This article talks about how the socio-philosophical views of Turkestan moderns were studied by Turkish scientists. It also talks about the research conducted by Turkish scientists.